ANALISIS DIMENSI KINERJA DINAS PENDAPATAN DAN PENGELOLAAN KEUANGAN DAERAH KOTA CIREBON - Yudha Adjie Brata; Nina Widowati; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The People Indonesia Demands against the good performance requires earnest effort to make it happen because the performance of the current govermment bureaucracy is still not the case shows high performance. This marked one of them is still of low quality of service given by bureaucracy to the people and this is also often accused as one of the factors the causes of fall of the country. As reported by the people’s Minds that revenues and service area (DPPKD) the City of Cirebon to mess around because of his difficult regulate advertising is not permitted. The lack of coordination of organizational performance in taking care of the PAD and may lead to a slowdown in overall development.This research uses qualitative, description to describe and analyze the performance of the department of revenue and financial management of the City of Cirebon area and description the dimensions that are available in the process of their performance. The collection of the data with the document, observation and interviews.Based on the result of the deliberations of research department of revenue and the financial management of the City of Cirebon region who has been describe in the previous chapter, it can be concluded that the performance of the department of revenue and the financial management of the City of Cirebon Area is already good because it already runs the principles of public administrasion and run their performance with a good organization coordination. DPPKD City of Cirebon’s performance in his job was always on the watch by community and other agencies so that the performance, the income and financial management of the City of Cirebon Area remains stable and able to maintain their performance.